2016
DOI: 10.1155/2016/7515721
|View full text |Cite
|
Sign up to set email alerts
|

DKA with Severe Hypertriglyceridemia and Cerebral Edema in an Adolescent Boy: A Case Study and Review of the Literature

Abstract: A 13-year-old adolescent boy with type 1 diabetes mellitus (1b) presented with diabetic ketoacidosis (DKA) and cerebral edema. Grossly lipemic serum and lipemia retinals due to extremely high triglyceride (TG) level were observed without evidence of xanthoma or xanthelasma. Cerebral edema was treated by appropriate ventilation and mannitol administration. Normal saline was carefully given and regular insulin was titrated according to blood sugar levels. Triglyceride levels were reduced from 9,800 mg/dL to norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…However, severe hypertriglyceridemia is rare, and clinicians should be aware that devastating consequences such as acute pancreatitis or lipidemia retinalis can occur. [3] Review of available literature has shown 12 previous children with severe hyperlipidemia with diabetic ketoacidosis, and acute pancreatitis was present in only eight cases [Table 2]. [34] Our case is the youngest case to present with the triad of severe hyperlipidemia, acute pancreatitis, and diabetic ketoacidosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, severe hypertriglyceridemia is rare, and clinicians should be aware that devastating consequences such as acute pancreatitis or lipidemia retinalis can occur. [3] Review of available literature has shown 12 previous children with severe hyperlipidemia with diabetic ketoacidosis, and acute pancreatitis was present in only eight cases [Table 2]. [34] Our case is the youngest case to present with the triad of severe hyperlipidemia, acute pancreatitis, and diabetic ketoacidosis.…”
Section: Discussionmentioning
confidence: 92%
“…[3] Review of available literature has shown 12 previous children with severe hyperlipidemia with diabetic ketoacidosis, and acute pancreatitis was present in only eight cases [Table 2]. [34] Our case is the youngest case to present with the triad of severe hyperlipidemia, acute pancreatitis, and diabetic ketoacidosis. The risk of mortality in severe diabetic ketoacidosis is much higher in children below 5 years and association with hyperlipidemia, and acute pancreatitis can further increase this risk.…”
Section: Discussionmentioning
confidence: 99%
“…In many case reports, severe HTG is observed during DKA associated with newly diagnosed T1D [5, 6] or attributed to poor diabetes control [7] with severe insulin deficiency. In our case, the fact that his HbA1c was 11.5% signifies insulin deficiency for months, even if he did not report discontinuing his insulin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Severe hypertriglyceridaemia can increase risk of acute pancreatitis, especially in patients with triglycerides levels higher than 1,000 -1,722 mg/dl. 2 Prevalence of severe hypertriglyceridaemia was found in about 8% of adults with diabetic ketoacidosis, 3 but few data have been reported in children with severity ranging from asymptomatic to severe acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%